Remote sensing of alpine glaciers in visible and infrared wavelengths: a survey of advances and prospects. Issue 5 (27th May 2016) - Bhardwaj, Anshuman; Joshi, P.K.; Sam, Lydia; , Snehmani
Abstract : Remote sensing is an efficient tool for temporal monitoring of inaccessible alpine glacial terrain. This study discusses the methods of remote sensing in visible and infrared (IR) wavelengths, which are helpful in providing important information about alpine glaciers. The scope of this study covers recent advances and prospects in optical and thermal remote sensing of glacier facies, glacier velocity, mass balance, glacial hazards and automated mapping techniques. The technology is ever evolving with the advent of new remote sensors capturing data in visible/IR wavelengths and better digital computing technology. An extensive list of significant studies further helps the reader to explore a particular topic of interest. We survey recent advances in this field and additionally highlight the emerging prospects.